The Effect of Work Environment and Work Discipline on Employee Performance (Case Study on CV. Jamal Handy Craft Rajapolah Tasikmalaya) - Adi Robith Setiana; Aldi (Nusantara Journal Of Management Business (NUMABI), 2023)
This study aims to determine the effect of the work environment and work discipline on employee performance (Case Study at CV. Jamal Handy Craft Rajapolah Tasikmalaya. This research uses non-parametric research methods with a quantitative approach and a qualitative approach (Mix Methode) with a planned research location at CV. Jamal Handy Craft is located at Jalan Raya Rajapolah No. 315 Margasari Rajapolah, Tasikmalaya Regency. The results showed that from the calculation results of SPSS.25 it was obtained that fcount was 88.588 while ftable was 3.21 meaning fcount > ftable. Then it can be concluded that Ho is rejected and Ha is accepted. This shows that the variables Work Environment and Work Discipline have a positive and significant effect on CV. Jamal Handy Craft Rajapolah Tasikmalaya.